Dental microstructure records life history events: A histological study of mandrills (Mandrillus sphinx) from Gabon. Issue 158 (September 2021) - Lemmers, Simone A.M.; Dirks, Wendy; Street, Sally E.; Ngoubangoye, Barthélemy; Herbert, Anaïs; Setchell, Joanna M.
Abstract: Accentuated lines in dental microstructure are hypothesized to correlate with potentially stressful life history events, but our understanding of when, how and why such accentuated lines form in relation to stressful events is limited. We examined accentuated line formation and life history events in the teeth of three naturally deceased mandrills ( Mandrillus sphinx, Cercopithecidae), for whom we had detailed life history information. We determined the ages at formation of accentuated lines in histological tooth sections and used dates of birth and death to calibrate dental histology to calendar time and individual age. We found accentuated lines that matched their mother's resumption of sexual cycles in two individuals, and possibly in the third individual. The subjects also formed lines when their mothers were mate-guarded by males or wounded. Accentuated lines matched the birth of the next sibling in one of two cases. Both females formed accentuated lines when they experienced their own sexual swelling cycles, but lines did not match all sexual swelling cycles. Mate-guarding matched an accentuated line in one case, but not in another. Lines matched all three parturitions in the two females. Changes in alpha male and captures did not consistently coincide with accentuated line formation, but repeated captures were associated with lines. Using simulated data, we show that the observed number of matches between lines and events would be very unlikely under a null hypothesis of random line formation. Our results support the hypothesis that some life history events are physiologically stressful enough to cause accentuated line formation in teeth. They contribute to our understanding of how primate life histories are recorded during dental development and enhance our ability to use teeth to reconstruct life history in the absence of direct observation.